An Efficient Synthesis of Substituted Pyrazoles from One-Pot Reaction of Ketones, Aldehydes, and Hydrazine Monohydrochloride - Lellek, Vit; Chen, Cheng-yi; Yang, Wanggui; Liu, Jie; Ji, Xuebao; Faessler, Roger (Synlett, 2018)
An efficient, one-pot and metal-free process for the preparation of 3,5-disubstituted and 3,4,5-trisubstituted pyrazoles on multi-gram scale was developed. One-pot condensation of ketones, aldehydes and hydrazine monohydrochloride readily formed pyrazoline intermediates under mild conditions. Oxidation of pyrazolines, in situ, employing bromine afforded a wide variety of pyrazoles. The methodology offers a fast, and often chromatography-free protocol for the synthesis of 3,4,5-substituted pyrazoles in good to excellent yields. Alternatively, a more benign oxidation protocol affords 3,5-disubstituted or 3,4,5-trisubstituted pyrazoles by simply heating pyrazolines in DMSO under oxygen.
Keywords: heterocyclic compounds; pyrazoles; pyrazolines; ketones; aldehydes; oxidation of pyrazolines; oxygen; bromine